Splenic SUMO1 controls systemic inflammation in experimental sepsis - Youssef, Ayman; Mohammed, Bilal Khan; Prasad, Abhishek; del Aguila, Angela; Bassi, Gabriel; Yang, Wei; Ulloa, Luis (Frontiers in Immunology, 2023)
Introduction The recent discovery of TAK981(Subasumstat), the first-in-class selective inhibitor of SUMOylation, enables new immune treatments. TAK981 is already in clinical trials to potentiate immunotherapy in metastatic tumors and hematologic malignancies. Cancer patients have more than ten times higher risk of infections, but the effects of TAK981 in sepsis are unknown and previous studies on SUMO in infections are conflicting. Methods We used TAK981 in two sepsis models; polymicrobial peritonitis (CLP) and LPS endotoxemia. Splenectomy was done in both models to study the role of spleen. Western blotting of SUMO-conjugated proteins in spleen lysates was done. Global SUMO1 and SUMO3 knockout mice were used to study the specific SUMO regulation of inflammation in LPS endotoxemia. Splenocytes adoptive transfer was done from SUMO knockouts to wild type mice to study the role of spleen SUMOylation in experimental sepsis. Results and discussion Here, we report that inhibition of SUMOylation with TAK981 improved survival in mild polymicrobial peritonitis by enhancing innate immune responses and peritoneal bacterial clearance. Thus, we focused on the effects of TAK981 on the immune responses to bacterial endotoxin, showing that TAK981 enhanced early TNFα production but did not affect the resolution of inflammation. Splenectomy decreased serum TNFα levels by nearly 60% and TAK981-induced TNFα responses. In the spleen, endotoxemia induced a distinct temporal and substrate specificity for SUMO1 and SUMO2/3, and both were inhibited by TAK981. Global genetic depletion of SUMO1, but not SUMO3, enhanced TNFα production and metabolic acidosis. The transfer of SUMO1-null, but not wild-type, splenocytes into splenectomized wild-type mice exacerbated TNFα production and metabolic acidosis in endotoxemia. Conclusion These results suggest that specific regulation of splenic SUMO1 can modulate immune and metabolic responses to bacterial infection.